Exposure to adversity and inflammatory outcomes in mid and late childhood - Meredith O'Connor (Brain, Behavior, & Immunity - Health, 2020)
Background: We aimed to estimate the association between exposure to adversity and inflammatory markers in mid (4 years) and late (11–12 years) childhood, and whether effects differ by type and timing of exposure. Methods: Data sources: Barwon Infant Study (BIS; N = 510 analyzed) and Longitudinal Study of Australian Children (LSAC; N = 1156 analyzed). Exposures: Adversity indicators assessed from 0 to 4 (BIS) and 0–11 years (LSAC): parent legal problems, mental illness and substance abuse, anger in parenting responses, separation/divorce, unsafe neighborhood, and family member death; a count of adversities; and, in LSAC only, early (0–3), middle (4–7), or later (10–11) initial exposure. Outcomes: Inflammation quantified by high sensitivity C-reactive protein (hsCRP, Log (ug/ml)) and glycoprotein acetyls (GlycA, Log (umol/L)). Analyses: Linear regression was used to estimate relative change in inflammatory markers, adjusted for sociodemographic characteristics, with exposure to adversity. Outcomes were log-transformed. Results: Evidence of an association between adversity and hsCRP was weak and inconsistent (e.g., 3+ versus no adversity: BIS: 12% higher, 95%CI -49.4, 147.8; LSAC 4.6% lower, 95%CI: −36.6, 48.3). A small positive association between adversity and GlycA levels was observed at both 4 years (e.g., 3+ versus no adversity: 3.3% higher, 95%CI -3.0, 9.9) and 11–12 years (3.2% higher, 95%CI 0.8, 5.8). In LSAC, we did not find evidence that inflammatory outcomes differed by initial timing of adversity exposure. Conclusions: Small positive associations between adversity and inflammation were consistently observed for GlycA, across two cohorts with differing ages. Further work is needed to understand mechanisms, clinical relevance, and to identify opportunities for early intervention.